FAKTOR-FAKTOR RISIKO DESIGN AND BUILD YANG MEMPENGARUHI KESUKSESAN PROYEK REHABILITASI TOTAL GEDUNG PENDIDIKAN DI PROVINSI DAERAH KHUSUS IBUKOTA JAKARTA - Andi M. Tarigan; Abdullah Abdullah; Hafnidar A.Rani (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Implementation of projects with system design and build, faced with various risks. These risks include no supporting data such as geological maps, soil investigation data, basic design drawings, and environmental documents, and difficulties in measuring job performance. These risks, can affect the success of the project. The success of the project is marked by the budget conformity with the actual cost, the conformity of the time plan with the time of implementation, the quality in accordance with the specifications, and the satisfaction of the parties involved in the project. This study aims to analyze the relationship and influence between design and build risk factors on project success, as well as to identify the dominant factors in design and build risk that affect the success of the total educational building rehabilitation project in package 4 in DKI Jakarta Province. Package 4 includes 18 units of SDN buildings, and 2 units of SMP buildings. This study used qualitative methods quantized through questionnaires, where the respondents were directed to 30 Construction Management (MK), and 17 personnel owners with a total of 47 respondents. The design and build risk factors analyzed in this research are owner owner management factor, procurement process, planning ability, implementation capability, project manager capability, and project scope factor. Validity and reliability test results show all valid question items and reliable variables. The result of the research shows that the scope of the project has a very low relationship, ownership management ability factor, implementation ability and project manager capability have low relation, planning ability factor has enough relationship, and procurement process factor has high correlation to project success. The design and build risk factors all had a significant effect on the project's success of 69.8%. The dominant factor in design and build risk affecting project success is the procurement process factor. This indicates that if the procurement process factor can be handled by the owner and the auction committee, then the success of the project will increase.